Improvement of hardness on butt weld joints aluminium alloy AA 6061 using the underwater friction stir weld (UFSW) method - Tamin, Norfauzi; Mohd Salleh, Muhammad; Azlan, Umar Al-Amani; Othman, Mohd Hairizal; Darmawan, Agung Setyo; Wan Abdul Malik, Wan Abdul Hafiz (Universiti Teknologi MARA, 2024)
This study reveals the hardness improvement resulting from Underwater Friction Stir Welding (UFSW) on the butt joint method AA 6061. Underwater welding introduces complexity to the joint's hardness due to the presence of water, which affects the welding process and the quality of the joint formed. The objective of the UFSW study is to explore potential advantages in the aquatic environment, primarily to obtain the optimal machine tilt angle. The study used a conventional milling machine with various spindle speeds, feed rates, and tilt angles to get the best combination of parameters. The spindle speed of 750 rpm, welding speed of 20 mm/min, and machine head angle of 2° recorded show the Brinell hardness (HRB) of UFSW to be 98.8% better than Friction Stir Welding (FSW) on various parameters. This study revealed that a machine tilt angle of 2° increased the hardness of UFSW welding. The results show that UFSW can increase HRB through proper head tilt angle, which is even better than the existing method, which is FSW.